2023
DOI: 10.1021/acs.jchemed.2c01069
|View full text |Cite
|
Sign up to set email alerts
|

Features of Immersive Virtual Reality to Support Meaningful Chemistry Education

Abstract: One way of triggering students' interest in chemistry is making chemistry education more meaningful. Four characteristics of meaningful chemistry education (MCE) were identified in projects that involved a redesign of curriculum materials: daily life context, the need-toknow principle, students' input, and the macro−micro connection. Chemistry education has struggled with the implementation of meaningful learning. A possible solution might be the use of immersive virtual reality (IVR) in chemistry classrooms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…In addition, the main research areas that we found in mapping are Education and Educational Research , Computer Science , and Engineering (Figure a). It should be noted that these areas are also strongly linked to research in technological fields, including the applications of VR and augmented reality in education. , In this context, the creativity and ingenuity of chemistry educators have been challenged by the emergence of the pandemic caused by SARS-CoV-2 to meet the needs and requirements of learners of chemistry. For example, student learning in laboratory settings , and the role of collaborative learning, including both problem-solving and laboratory activities …”
Section: Discussionmentioning
confidence: 99%
“…In addition, the main research areas that we found in mapping are Education and Educational Research , Computer Science , and Engineering (Figure a). It should be noted that these areas are also strongly linked to research in technological fields, including the applications of VR and augmented reality in education. , In this context, the creativity and ingenuity of chemistry educators have been challenged by the emergence of the pandemic caused by SARS-CoV-2 to meet the needs and requirements of learners of chemistry. For example, student learning in laboratory settings , and the role of collaborative learning, including both problem-solving and laboratory activities …”
Section: Discussionmentioning
confidence: 99%
“…A side conversation discussed the potential role of virtual reality (VR) in education. 120,121 One panelist highlighted the use of VR in classes to enhance students' understanding of internal structures and processes within battery cells, as well as assist in building crystal structures. The discussion also touched upon the application of VR in outreach programs.…”
Section: Educationmentioning
confidence: 99%
“…By tracking article citations, educators and learners can efficiently determine the interdisciplinary value of the work by categorizing which fields cited the published article. In addition, citation tracking offers several advantages, including assessing research impact and visibility, enabling efficient resource allocation, and introducing emerging trends and fields, for example, cheminformatics and related disciplines . It also aids in building on prior research, fosters collaborations, and ensures scientific work quality.…”
Section: Introductionmentioning
confidence: 99%